Перспективи атомної енергетики України в умовах сталого розвитку - Бойко, В.; Міскевич, І. (Економіка природокористування і сталий розвиток, 2021)
Досліджено сучасні перспективи атомної енергетики України в умовах сталого розвитку. Зазначено, що українська енергетика перебуває на межі кризи. Низка викликів, з якими зіштовхнулася наша держава, не сприяють ефективному розв’язанню проблем у галузі й лише розширюють їх масштабність і спектр, зокрема в екологічному аспекті. Аргументовано, що розвиток атомної енергетики можна вважати засобом, який гарантуватиме Україні енергетичну безпеку та знизить залежність від зовнішнього постачання природного газу й вугілля.
Наголошено на стратегічному значенні атомної енергетики для держави. Окреслено її переваги в контексті зовнішніх витрат на виробництво електроенергії порівняно з іншими технологіями енергогенерації.
Так, з’ясовано, що супутні витрати, пов’язані з виробництвом електроенергії на станціях, які працюють на вугіллі, набагато вищі, ніж на АЕС. Більше того, витрати, спричинені кліматичними змінами, за даними дослідників, у сонячної енергетики більші у понад 4 рази. Зауважено, що впродовж останніх 10 років ситуація дещо змінилася і технології, зокрема стосовно ефективності акумуляторів і технологій їх переробки, значно покращилися, проте атомна енергетика не втрачає вигідних позицій.
Виявлено основні виклики для енергетичної системи України: зношеність і вплив на навколишнє природне середовище теплової генерації; незадовільні темпи модернізації основних генеруючих потужностей, переважно ТЕС; невідповідність гнучкості об’єднаної енергетичної системи розвитку зеленої енергетики; незадовільні темпи й масштаби впровадження відновлюваної енергетики.
Проаналізовано складові атомно-енергетичного комплексу України. Визначено основні перспективи розвитку атомної енергетики, що насамперед стосується добудови 3 і 4 енергоблоків Хмельницької АЕС, а також будівництва малих модульних реакторів. Запропоновано узагальнену концептуальну модель гібридної енергогенерації, основою якої є відновлювана та атомна енергетика, здатні відігравати роль маневрового (балансувального) джерела електроенергії. This article examines the current prospects for developing nuclear energy in Ukraine in terms of sustainable development. The strategic importance of nuclear energy for Ukraine is indicated. The advantages of nuclear energy in the context of electricity production's external costs over other energy generation technologies are noted. Today, nuclear energy is considered the most cost-effective low-carbon energy source. An analysis of reports from the Atomic Energy Agency and the US Department of Energy shows that nuclear power generation is a leader in many countries' energy sector, producing cheaper electricity than traditional TPPs. The main challenges for the energy system of Ukraine are highlighted. Among them are: wear and tear and impact on the environment of thermal generation (equipment at thermal power plants is worn out by 70–90 %); the unsatisfactory pace of modernization of the main generating capacities, mainly TPPs; the inconsistency of the flexibility of the United Energy System (UES) of Ukraine with the development of "green" energy (increasing the share of "green" energy increases the risks of UES sustainability) and the corresponding ill-consideredness in the pace and scale of renewable energy implementation. Lack of shunting power; the need to duplicate the capacity of renewable energy due to the low installed capacity factor (ICUF) and significant dependence on natural and climatic conditions; the need to replace existing nuclear power units, which end their extended service life with new, more modern ones that will meet the latest safety and economy standards; the imperfection of the electricity market, primarily in the context of its sale by nuclear generation producers under bilateral agreements; deficit of investments in the whole fuel and energy complex.
The main prospects for the development of nuclear energy in Ukraine are identified. Completion of Units 3 and 4 of Khmelnytskyi NPP (KhNPP) remains a critical prospect. An obstacle to this for Ukraine is the lack of appropriate technologies on the Ukrainian side and the curtailment of cooperation with Russia and companies belonging to this state. Another obstacle is that the promising power units of KhNPP based on WWER-1000 belong to the second generation, which today do not morally meet the latest trends and requirements in efficiency and safety standards. Theoretically, Western leaders in the nuclear industry, Orano and Westinghouse, could develop nuclear power plants based on their next-generation "3" and "3+" reactors, where the essential safety requirements are already embedded in the original design of the unit.
Another option would be to implement a small modular reactor technology project in Ukraine. Technologically, this will quickly resolve the issue of load management, which arose due to the rapid increase in the share of renewable energy generation in our country. This type of reactor has a significant advantage, which in addition to the minimum load on the environment is: the possibility of placement in areas where additional services are needed in the energy market; low construction costs; frequency of service and operating time; the full cycle of work with fuel. In general, low-power reactors can be used to implement the strategy of hybrid power generation (renewable + nuclear energy).